Mismatch negativity-indexed auditory change detection of speech sounds in early and chronic schizophrenia. (30th May 2019) - Fisher, Derek J.; Rudolph, Erica D.; Ells, Emma M.L.; Knott, Verner J.; Labelle, Alain; Tibbo, Philip G.
Abstract : Auditory mismatch negativity (MMN) assessed with phonetic (vowel) stimuli. Early schizophrenia patients did not exhibit a reduced MMN (vs. controls). Chronic schizophrenia patients did exhibit a reduced MMN (vs. controls). Abstract: Auditory change detection, as indexed by the EEG-derived mismatch negativity, has been demonstrated to be dysfunctional in chronic schizophrenia using both pure-tone and speech (phoneme) sounds. It is unclear, however, whether reduced MMN amplitudes to speech sound deviants are observed within the first 5 years of the illness. The present study investigated MMNs elicited by across-vowel (phoneme) change in early schizophrenia (ESZ; Experiment 1) as well as chronic schizophrenia (CSZ; Experiment 2). In both experiments, clinical and control participants were presented the Finnish phoneme /e/ (standard; P = .90) and the Finnish phoneme /ö/ (deviant; P = .10) within an oddball paradigm. In experiment 2 we report significantly reduced MMN amplitudes in CSZ relative to HCs, but no differences were found when comparing ESZ and HC in experiment 1. Additionally, in our clinical samples, MMN amplitudes were correlated with symptom scores. These findings suggest that early detection of phonetic change may be impaired in chronic schizophrenia, but not early in the progression of the illness. As MMN reductions only emerged in patients with a longer course of illness, and appeared to change with symptom severity, this suggests a dynamic change in the early auditory processing of language over time in schizophrenia. Graphical abstract: Image, graphical abstract